2008
DOI: 10.1007/s00425-008-0815-0
|View full text |Cite
|
Sign up to set email alerts
|

Neutral invertases in grapevine and comparative analysis with Arabidopsis, poplar and rice

Abstract: Neutral invertases (NIs, EC 3.2.1.26) cleave sucrose to glucose and fructose. They are encoded by a small gene family of 9 members in the Arabidopsis genome, 8 in rice, 16 in poplar and 9 in Vitis vinifera (L.). The grapevine NIs were identified in the 8.4X genome assembly of the quasi-homozygous line PN40024. In addition, alleles of three NIs were sequenced in the heterozygous cultivar 'Cabernet Sauvignon'. Analyses of sequence variation between alleles, homoeologous and paralogous copies in grapevine and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 57 publications
4
48
0
Order By: Relevance
“…In fact, the annotated genome sequence of Vitis vinifera become available (Velasco et al, 2007), suggesting that grapevine has a potential as a model organism for fruit trees. In addition, with the availability of complete grapevine sequences, it has become imperative to compare the functions of gene families, particularly those having vital functions with the gene families characterized from Arabidopsis (The French-Italian Public Consortium for Grapevine Genome Characterization, 2007;Matus et al, 2008;Nonis et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the annotated genome sequence of Vitis vinifera become available (Velasco et al, 2007), suggesting that grapevine has a potential as a model organism for fruit trees. In addition, with the availability of complete grapevine sequences, it has become imperative to compare the functions of gene families, particularly those having vital functions with the gene families characterized from Arabidopsis (The French-Italian Public Consortium for Grapevine Genome Characterization, 2007;Matus et al, 2008;Nonis et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Although some supercontigs are still being correctly assembled and oriented in each chromosome (Matus et al, 2008), the completion of the grapevine genome has made it possible to identify gene family through the analysis of sequence similarity with Arabidopsis genome. In fact, terpene synthase gene family (The French-Italian Public Consortium for Grapevine Genome Characterization, 2007), MYB R2R3 subfamily (Matus et al, 2008) and invertase (Nonis et al, 2008) have been identified by In-silico analysis based on Arabidopsis genome. Recently, putative rice and poplar MAPKs, which are placed into four subgroups that are identified earlier in Arabidopsis based on the sequence similarity, have been revealed through in-silico analysis of current rice and poplar genome databases Nicole et al, 2006;Reyna and Yang, 2006;Liu and Xue, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The plant neutral invertases have generally been attributed a cytosolic localization, consistent with the neutral pH activity optimum and absence of glycosylation, and have recently been classified into two subgroups, a and b, with the a subgroup associated with organelles, plastids and mitochondria, while the b subgroup has been attributed a non-organellar localization (Ji et al 2005;Murayama and Handa 2007;Nonis et al 2008;Vargas et al 2008). Figure 2 indicates that the four expressed genes represent the three subgroups of neutral invertase: CmNIN3 is most similar to the b-type cytosolic form, CmNIN1 and CmNIN4 are a-type, mitochondrial and CmNIN2 encodes for an a-type plastidic enzyme.…”
Section: Invertasesmentioning
confidence: 98%
“…2). Melon representatives of the three clades of NIN (Ji et al 2005;Murayama and Handa 2007;Nonis et al 2008;Vargas et al 2008), two clades of UGE (Barber et al 2006;Rösti et al 2007), two groups of FK , three groups of SUS Núñez et al 2008;Subbaiah et al 2006) and two groups of HK (Claeyssen and Rivoal 2007;Granot 2008;Olsson et al 2003) were all identified. The SPS gene family, which has been divided into three subfamilies, A, B and C (Komatsu et al 1999;Langenkämper et al 2002;Lutfiyya et al 2007) is the only exception.…”
Section: Gene Families and Functionalizationmentioning
confidence: 99%
See 1 more Smart Citation